Instruction Modes for Motor Control Skills Acquisition: A Randomized Controlled Trial. Issue 4 (3rd July 2020) - La Touche, Roy; Sánchez-Vázquez, Macarena; Cuenca-Martínez, Ferran; Prieto-Aldana, María; Paris-Alemany, Alba; Navarro-Fernández, Gonzalo
Abstract: The objective was to compare two different instruction modes used to teach patients with nonspecific chronic low back pain (CLBP) to perform a lumbar motor control task. The three intervention instruction modes used were: common verbal explanation of a motor task based on a motor control therapeutic exercise (MCTE-control group), MTCE instructed using motor imagery (MI) and MCTE instructed using tactile feedback (TF). The main outcome measure was lumbar motor control of the neutral position test. Forty-eight patients with CLBP were randomly allocated into three groups of 16 patients per group. The MI strategy was the most effective mode for developing the motor control task in an accurate and controlled manner, obtaining better outcomes than TF or verbal instruction.